2017
DOI: 10.4067/s0716-10182017000500494
|View full text |Cite
|
Sign up to set email alerts
|

Dengue en un neonato

Abstract: Dengue is the disease transmitted by arthropods of major importance in public health; however its presence in the neonatal stage is poorly studied, with few cases described worldwide. We present the case report of a neonate who started illness at 12 days of age, characterized by fever and irritability. He was hospitalized for suspicion of neonatal sepsis; later he presented thrombocytopenia and due the antecedent of his mother with diagnosis of dengue after childbirth, dengue tests were obtained in the neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Prevention is based on immunization and vector control, with proper disposal of solid waste and improved water storage practices to prevent female mosquitoes from laying eggs. 5 In April 2023, the National Drug, Food and Technology Administration of Argentina (Administración Nacional de Medicamentos, Alimentos y Tecnología Médica, ANMAT) approved the use of a dengue vaccine developed by Japanese pharmaceutical company Takeda, for individuals aged 4 years and older, whether or not they suffered from dengue fever before. The vaccine is called TAK-003.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention is based on immunization and vector control, with proper disposal of solid waste and improved water storage practices to prevent female mosquitoes from laying eggs. 5 In April 2023, the National Drug, Food and Technology Administration of Argentina (Administración Nacional de Medicamentos, Alimentos y Tecnología Médica, ANMAT) approved the use of a dengue vaccine developed by Japanese pharmaceutical company Takeda, for individuals aged 4 years and older, whether or not they suffered from dengue fever before. The vaccine is called TAK-003.…”
Section: Discussionmentioning
confidence: 99%
“…La prevención se sustenta en la inmunización y el control vectorial, con la eliminación adecuada de los residuos sólidos y la mejora de las prácticas de almacenamiento de agua, para evitar que los mosquitos hembras depositen sus huevos. 5 La Administración Nacional de Medicamentos, Alimentos y Tecnología Médica (ANMAT) aprobó en abril de 2023 el uso de la vacuna contra el dengue desarrollada por el laboratorio japonés Takeda para mayores de 4 años, hayan cursado o no previamente la enfermedad. El nombre de la vacuna es TAK-003.…”
Section: Discussionunclassified
“…Intrauterine growth restriction, premature placental detachment, preterm birth, miscarriage, and stillbirth have been associated with maternal infection [ 2 , 10 , 17 ]. Vertical transmission is thought to occur with infections in later pregnancy and yield varied manifestations in the neonate, ranging from subclinical infections to dengue hemorrhagic fever and dengue shock syndrome [ 18 , 19 ]. Prior DENV infections have shown protective effects against ZIKV congenital infection in human studies; however, animal models have demonstrated an enhanced risk of congenital transmission in this scenario [ 20 ].…”
Section: Introductionmentioning
confidence: 99%